Analysis Of Factors Causing Lateness To School In Grades III And V Of SDN 06/Ii Tanjung Agung And Its Impact On Learning Outcomes - Nuras, Fadhlan Ramadhan; Apdoludin, Apdoludin; Subhanadri, Subhanadri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to identify and analyze the underlying causes of student tardiness and its impact on learning outcomes among Grade III and Grade V students at SDN 06/II Tanjung Agung. Employing a qualitative descriptive method, data were collected through observation, interviews with teachers and students, and documentation of attendance records. The findings indicate that tardiness is caused by both internal factors such as oversleeping, lack of time discipline, and poor sleep habits and external factors, including long commuting distances, transportation issues, and family responsibilities. These delays often result in students missing core subject explanations, reducing their understanding and academic performance. Teachers generally respond with verbal warnings and counseling, though responses vary depending on frequency and student behavior. The study concludes that addressing student tardiness requires a collaborative effort involving both school and family, with an emphasis on behavioral support, routine reinforcement, and context sensitive educational policies. These findings can inform school strategies and educational policymaking to foster student punctuality and improve learning engagement.